2010
DOI: 10.4314/ajtcam.v7i3.54776
|View full text |Cite
|
Sign up to set email alerts
|

New antitrypanosomal tetranotriterpenoids from <i>Azadirachta Indica</i>

Abstract: Organic extracts of the leaves of Azadirachta indica A. Juss. yielded ten antitrypanosomal terpenoids. Three of these (1 -3), are novel and are derivatives of nimbolide and nimbin. They were extracted from chloroform fraction of methanol extract. These compounds were found to exhibit strong antitrypanosomal activities against Trypanosoma brucei rhodesiense with MIC values ranging of 6.9, 15.6 and 7.8 µg/ml respectively and were more active than Cymerlarsan ( a standard drug), which had an MIC value of 187.5 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Limonoids are characteristic phytochemicals of the Meliaceae, including Carapa procera ( Table S6 ) [40] , [57] , and numerous limonoids have exhibited antiprotozoal activities [58] [62] . Six of the eleven C. procera limonoids showed notably strong docking with TbCYP51 (docking energies<−26 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…Limonoids are characteristic phytochemicals of the Meliaceae, including Carapa procera ( Table S6 ) [40] , [57] , and numerous limonoids have exhibited antiprotozoal activities [58] [62] . Six of the eleven C. procera limonoids showed notably strong docking with TbCYP51 (docking energies<−26 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies has shown the in vitro efficacy of the seco -limonoid compound 11 α ,19 β -dihydroxy-7-acetoxy-7-deoxoichangin using the murine macrophage cell line J774·2 as target cell of in vitro infection (Coy Barrera et al 2011), accompanied by an immunomodulatory effect on infected phagocytic cells (murine macrophage and human dendritic cells), which appears to lead to the ‘reactivation’ of the microbicidal capability of infected cells (Granados-Falla et al 2013). In this sense, other studies support the need to confirm the data obtained in in vitro assays by limonoid compounds (as Gedunin, 7-deacetylgedunin and 7-oxo-7-deacetylgedunin) for which over the past years, its potential antiparasitic activity have been assessed against species belonging to the genus Plasmodium, Trypanosoma and Leishmania (Rosas, 2005; Hay et al 2007; Batista et al 2009; Githua et al 2010).…”
Section: Introductionmentioning
confidence: 87%
“…The extracts were assayed on the three trypanosome strains at concentration ranges of 4000 -1000µg/ml. Each plate was examined with an inverted microscope to determine the minimum inhibitory concentration (MIC) which is the concentration at which no cell with a normal morphology and/or motility was found in comparison to the negative control cultures (Githua et al, 2010).…”
Section: In Vitro Assays For Anti-trypanosomal Activitymentioning
confidence: 99%